TI_GERICHTE 72.2007.113 vom 14. Dezember 2007 , Procedura abbreviata ex art. 316a ss. CPP - appropriazione indebita ripetuta - TI Tribunale d'appello (2007)
Procedura abbreviata ex art. 316a ss. CPP - appropriazione indebita ripetuta